Cerita Baru Klinting di Desa Banyubiru Kecamatan Ambarawa Kabupaten Semarang: Tinjauan Estetika Resepsi - Muhammad Radhitya Kusuma Negara; Joko Sujarwo; Gibson Samuel Imbenai; Tegar Taryan Margatama; Rizky Kusumo Adi; Yunior Dhian Bagaskara; Dwi Susanto (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2024)
The psychological impact of oral literature, particularly the Baru Klinting folklore, on readers has been understudied, especially in relation to material objects associated with the story. This study aims to investigate the psychological effects of the Baru Klinting story on residents of Banyubiru Village, Ambarawa District, Semarang Regency. A qualitative-descriptive approach was employed, focusing on a single subject, Suryana, a resident of Banyubiru Village. Data was collected through recorded interviews and note-taking. Analysis was conducted using a combination of reception aesthetics theory and psychoanalysis. The study revealed three key findings: (1) The subject, not being a literary expert, perceived the story as factual; (2) The subject showed little interest in literature but regularly participated in local traditions like swamp alms; (3) The Baru Klinting story, functioning as a collective unconscious and supported by personal unconscious complexes, led the subject to struggle in distinguishing fiction from reality. This resulted in individualization manifesting as resistance through persona, exemplified by participation in swamp alms preservation. The subject exhibited signs of psychosis, highlighting the profound psychological impact of oral literature on individuals lacking literary expertise. This study underscores the need for further research on the intersection of folklore, psychology, and community traditions.